Multivitamin, mineral, and n-3 PUFA supplementation to reduce aggression among long-stay psychiatric inpatients: a randomized clinical trial - N. De Bles; N. Rius-Ottenheim; A. Van Hemert; E. Giltay (European Psychiatry, 2022)
Introduction Aggression and violent incidents are a major concern in psychiatric inpatient care. Nutritional supplementation was found to reduce aggressive incidents and rule violations in forensic populations and in children with behavioral problems.